Factors Affecting Whether Or Not Cancer Patients Consider Using Acupuncture. Issue 2 (April 2017) - Oh, Byeongsang; Eade, Thomas; Kneebone, Andrew; Pavlakis, Nick; Clarke, Stephen; Eslick, Guy; River, Jo; Back, Michael
Objective: To explore the factors associated with utilisation of an acupuncture service in a tertiary oncology setting in an Australian public hospital. Method: Cancer patients attending oncology clinics at a university teaching hospital were invited to participate in the evaluation of acupuncture services from June 2014 to May 2015. Patients had a prior diagnosis of cancer (albeit at different stages) and were planning to receive, or were already receiving, systemic and/or radiation cancer treatment. Results: The majority (81%) of participants indicated that they would consider the use of acupuncture during their cancer treatment. The most common reasons given for not considering acupuncture included adequate control of symptoms already with medical treatment, inconvenient clinic timing, and needle phobia. The main reasons given for considering acupuncture use included its perceived capability of reducing fatigue, boosting energy levels, improving immune function, and reducing pain and anxiety. Patients considering acupuncture use also demonstrated significantly higher levels of stress (p<0.001), anxiety and depression (p<0.001), fatigue (p<0.001), and lower global quality of life (p<0.01) compared to those who were not considering acupuncture. Conclusions: The findings show that demand for acupuncture by cancer patients is high. A substantial proportion of cancer patients intend to use acupuncture to manage cancer and/or cancer treatment-related symptoms. Discussion with patients about acupuncture and other complementary therapies during the consultation may improve cancer care.